The EU's Voice Beyond its Borders: The European Union's External Communication - Luminita Soproni; Ioan Horga (CES Working Papers, 2016)
The EU's developing global role demands a new approach to communications outside the Union. Besides communicating its policies to its citizens in order to enhance their trust in the idea of the United Europe, it is also extremely important to provide information regarding its policies and actions beyond its borders, to non-member countries and also to various international entities and organizations. This approach is necessary because the strength of an organization' (in our case the European Union's) external reputation depends not only on the core values embedded in its domestic culture, but also on the way how it communicates them to various target publics.The paper analyses the external communication of the European Union (lines of action, actors involved, and communication realized through different policies) and how it affects the external image of the region, demonstrating the need for a coherent communication strategy that combines the interests of Member States with those of the European institutions and the needs of internal public with those of external public.
Keywords: R1; R58; H77; M31; 330; European Union; global communication; visibility; image; strategy